DETERMINAN PEMILIHAN AUDITOR EKSTERNAL BERKUALITAS (Students' Journal of Accounting and Banking, 2014)
This study examined and analyzed the influence of the number of Board of Commissioners, the growth rate of the company, and the external financing needs of the election of the external auditors on the quality of manufacturing companies that went public in Indonesia.The population in this study are all companies engaged in the manufacturing sector which is registered in the Indonesian Stock Exchange (BEI) in 2010-2012. As many as 263 companies selected sample using purposive sampling technique. The analysis technique used is logistic regression.The results showed that the amount of BOC significant effect on the selection of the external auditor quality. While the rate of growth and external financing needs are not significant influence on the selection of the external auditor quality.Keywords: Board of Commissioners, Company Growth, External Financing Needs, Selection of Qualified External Auditors